Progress in the development of DNA vaccines against foot-and-mouth disease. (April 2012) - Fowler, Veronica L; Barnett, Paul V
DNA vaccines are, in principle, the simplest yet most versatile methods of inducing protective humoral and cellular immune responses. Research involving this type of vaccine against veterinary diseases began in the early 1990s and has since seen the evaluation of more than 30 important viral pathogens, including the economically important foot-and-mouth disease. With the demonstration that DNA vaccines protect against foot-and-mouth disease in sheep and pigs, and the advantages these DNA vaccines have over the conventional formulations, this approach may provide a better solution to the control of this disease. In this review, we provide a comprehensive overview of DNA vaccination strategies for foot-and-mouth disease reported in the literature, in which we highlight the studies that have reported protection in the key target species.